Interactive Multimedia Development Assisted by I Spring Suite 10 Integrated SETS (Science, Environment, Technology, Society) Approach to Improve High School Students' Critical Thinking Skill - Wandika; Yulkifli; Desnita; Yohandri; Siti Aisyah (Indonesia Approach Education, 2024)
The aim of this research is to develop interactive multimedia assisted by Ispring suite 10 integrated with the SETS approach that is valid, practical and effective in order to advance high school students' critical thinking skills. This type of research is research and development (R&D) using the ADDIE development model. The participants were class XI students. Science at SMAN 2 Padang. The research results show: 1) Validation of interactive multimedia reaches very valid criteria; 2) The practicality of interactive multimedia is determined through learning implementation of 89.74% with practical criteria and student response questionnaires of 87.40% with practical criteria; 3) Interactive multimedia assisted by Ispring Suite 10's integrated SETS approach can increase critical thinking capabilities effectively. The novelty of this research is that teachers can apply interactive multimedia assisted by Ispring suite 10 integrated SETS approach as one way to improve students' critical thinking skills.